2019
DOI: 10.1073/pnas.1904516116
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-mediated reflux of secretory proteins to the cytosol during endoplasmic reticulum stress

Abstract: Diverse perturbations to endoplasmic reticulum (ER) functions compromise the proper folding and structural maturation of secretory proteins. To study secretory pathway physiology during such “ER stress,” we employed an ER-targeted, redox-responsive, green fluorescent protein—eroGFP—that reports on ambient changes in oxidizing potential. Here we find that diverse ER stress regimes cause properly folded, ER-resident eroGFP (and other ER luminal proteins) to “reflux” back to the reducing environment of the cytoso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Together, these experiments argue that ER‐sfGFP enters the ER, undergoes SS cleavage and correct folding, and then is retrotranslocated by a mechanism that appears to be distinct from ERAD‐L. Furthermore, these data are in agreement with Igbaria et al that showed deletion of HRD1 , DOA10 (which is required for ERAD‐M for membrane proteins), as well as the resulting double mutant do not impair movement into the cytoplasm of ER‐localized GFP reporters during stress 14 . Thus, the phenomenon appears to be distinct from previously described forms of ERAD.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Together, these experiments argue that ER‐sfGFP enters the ER, undergoes SS cleavage and correct folding, and then is retrotranslocated by a mechanism that appears to be distinct from ERAD‐L. Furthermore, these data are in agreement with Igbaria et al that showed deletion of HRD1 , DOA10 (which is required for ERAD‐M for membrane proteins), as well as the resulting double mutant do not impair movement into the cytoplasm of ER‐localized GFP reporters during stress 14 . Thus, the phenomenon appears to be distinct from previously described forms of ERAD.…”
Section: Resultssupporting
confidence: 87%
“…Instead, we uncovered a novel pathway, distinct from ERAD, for the movement of correctly folded soluble ER proteins back to the cytoplasm. A similar concurrent study by the Papa group using the eroGFP reporter drew similar conclusions 14 . To distinguish this novel ER stress induced mechanism from canonical ERAD pathways, we have termed this phenomenon “ER reflux.”…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…First, as targets of ERO1‐PDI, rxYFP/roGFPs may also directly report on their activity independently of GSH . Second, the probe may wrongly report on ER redox modulation if mistargeted or refluxed from the ER to the cytosol upon stress . A solution is to tether the probe to the ER membrane .…”
Section: Approaches To Assess Er Stressmentioning
confidence: 99%